PENGARUH LEVERAGE, CASH FLOW, LIQUIDITY DAN GROWTH OPPORTUNITY TERHADAP CASH HOLDING - Hensu, Kent Evangelista; Nariman, Augustpaosa (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research aims to find empirical evidence regarding the impact of leverage, cash flow, liquidity and growth opportunities on cash holdings in the manufacturing industry infrastructure of companies listed on the Indonesia Stock Exchange for the 2019-2020 period. The sample was selected using a purposive sampling method, and the valid data consisted of 121 sample companies over a period of 3 years. Data is processed using SPSS (Statistical Product and Service Solution) version 22 for Windows and Microsoft Excel 2013. The results of the F test show that leverage, cash flow, liquidity and growth opportunities have a significant effect on cash reserves. The implications of this study indicate that all independent variables collectively are able to predict cash holdings. Partial testing reveals that leverage and cash flow show a positive and insignificant effect on cash holding, liquidity has a positive and significant effect on cash holding, growth opportunity has a negative and insignificant effect on cash holding.